METHODOLOGY FOR CHECKING THE SPEECH ACTIVITY OF STUDENTS WITH A WEAK PRIMARY SCHOOL MIND - Nabiyev Ravshanjon Shavkatjon ugli (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is covered on the basis of several techniques in the development of speech activity in mentally retarded students. In this, methods have been improved based on cognitive activity of mentally retarded students.